Investigation on Physical Properties of Ring-Type Wigglers Combined with a Miniaturized Column - Kumar Jha, Vinaya; Kim, Dae-Wook; Ahn, Seungjoon; Oh, Tae-Sik; Seob Kim, Ho; Chul Kim, Young (Asian Journal of Chemistry, 2013)
Characteristics of ring-type electrostatic wigglers for free electron radiation have been analyzed using a 3D simulation tool. The distribution of electric potential, electric field strength affects the motion of electron beam within a wiggler system and they are determined by the bias voltage and wiggler design. In this report, these factors are carefully investigated for a few ring-type wigglers and the results offer a criterion for optimization of ring type wigglers attached to a miniaturized electron column.